Sistem Pendukung Keputusan Penerimaan Beasiswa UKT Menggunakan Metode Analitychal Hierarchy Process (AHP) - Irsyadunas, Irsyadunas; Puspita, Lydia; Cahyani, Meriza; Nora, Silvia; Mahasyura, Figo; Syahputra, Yoss Prima (Journal of Student Development Information System (JoSDIS), 2022)
In Indonesia, the economy is one of the obstacles to sustainability in the education sector. thus forming a scholarship program. In determining scholarship recipients, a selection is carried out where there are several predetermined criteria. To get the best criteria in determining scholarship recipients, it can be done by using a Decision Support System with the Analytical Hierarchy Process method where the main input is human perception. The criteria used in this study were GPA, parents' income, number of family dependents, active students, and KTP which were very influential in determining scholarships. Each criterion will be given a level of importance, which can be done by comparing one criterion with another. The problem faced is that conventional data collection processes often occur errors. The purpose of the research is to prevent errors in data collection, and the process for results for scholarship recipients is more optimal. This research was conducted at PGRI University, West Sumatra in February 2023. This web-based Decision Support System was designed using the PHP programming language and MySQL database with XAMPP as the local server. The results of this study indicate that the criteria used greatly influence the determination of scholarship acceptance.